Gifsy-1 Prophage IsrK with Dual Function as Small and Messenger RNA Modulates Vital Bacterial Machineries - Hershko-Shalev, Tal; Odenheimer-Bergman, Ahuva; Elgrably-Weiss, Maya; Ben-Zvi, Tamar; Govindarajan, Sutharsan; Seri, Hemda; Papenfort, Kai; Vogel, Jörg; Altuvia, Shoshy (PLoS genetics, 2016)
While an increasing number of conserved small regulatory RNAs (sRNAs) are known to function in general bacterial physiology, the roles and modes of action of sRNAs from horizontally acquired genomic regions remain little understood. The IsrK sRNA of Gifsy-1 prophage of Salmonella belongs to the latter class. This regulatory RNA exists in two isoforms. The first forms, when a portion of transcripts originating from isrK promoter reads-through the IsrK transcription-terminator producing a translationally inactive mRNA target. Acting in trans, the second isoform, short IsrK RNA, binds the inactive transcript rendering it translationally active. By switching on translation of the first isoform, short IsrK indirectly activates the production of AntQ, an antiterminator protein located upstream of isrK. Expression of antQ globally interferes with transcription termination resulting in bacterial growth arrest and ultimately cell death. Escherichia coli and Salmonella cells expressing AntQ display condensed chromatin morphology and localization of UvrD to the nucleoid. The toxic phenotype of AntQ can be rescued by co-expression of the transcription termination factor, Rho, or RNase H, which protects genomic DNA from breaks by resolving R-loops. We propose that AntQ causes conflicts between transcription and replication machineries and thus promotes DNA damage. The isrK locus represents a unique example of an island-encoded sRNA that exerts a highly complex regulatory mechanism to tune the expression of a toxic protein.